Consensus-based translation, cultural adaptation, and validation of the Menopause Specific Quality of Life Questionnaire for menopausal women in Sri Lanka - Chithramali Hasanthika Rodrigo; Ruwan Ferdinando; Rohini De Alwis Seneviratne (College of Community Physicians of Sri Lanka, 2020)
Introduction: Quality of life during menopause could be affected by distressing menopausal symptoms. Menopause Specific Quality of Life Questionnaire (MENQOL) is an instrument developed to measure menopausal symptoms and their associated degree of bother. Objectives: To translate, culturally adapt and validate the Menopause Specific Quality of Life Questionnaire (MENQOL) for menopausal women of 45-55 years in Sri Lanka Methods: Translation, cultural adaptation, and validation of 29 items in MENQOL were carried out in three stages. The first stage involved translation of English version of the questionnaire into Sinhala language using a consensus-based nominal group process by a panel of five experts. In the second stage, cultural adaptation of the translated MENQOL questionnaire was carried out by conducting qualitative interviews with ten post-menopausal women of 45-55 years. In the third stage, construct validity of MENQOL was assessed in a community-based cross-sectional survey conducted among 174 postmenopausal women in 45-55 age group. Results: At the end of the translation process, the panel of experts agreed on the most appropriate translations through a voting process (consensus measurement), and appropriate translations were chosen by resolving disagreements (consensus development). The translated questionnaire named as MENQOLS was further modified based on inputs from the interviews with post-menopausal women. Principal component analysis of the validation study data resulted in a 26-item, five factor structure for MENQOL-S. Conclusions: MENQOL-S is conceptually and culturally appropriate for use in Sri Lanka. It could be used in community or healthcare settings to assess menopause specific quality of life among menopausal women and to assess outcome during intervention studies to improve their quality of life.